2017
DOI: 10.3389/fpsyg.2017.00443
|View full text |Cite
|
Sign up to set email alerts
|

Regional Gray Matter Volume Is Associated with Restrained Eating in Healthy Chinese Young Adults: Evidence from Voxel-Based Morphometry

Abstract: Highlight Participants were non-clinical young adults with different restrained eating levels.We assessed relations of restrained eating (RE) with regional gray matter volume (rGMV).High RE scores were related to larger GMV in specific areas related to reward.High RE scores were also linked to less GMV in regions related to response inhibition. Objective: Dieting is a popular method of weight control. However, few dieters are able to maintain initial weight losses over an extended period of time. Why do most r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…More specific to overeating behaviors, reduced OFC gray matter volume and thickness have been related to less restrained eating (Su, Jackson, Wei, Qiu, & Chen, 2017) and unhealthy food choice (Cohen, Yates, Duong, & Convit, 2011), although one study reported larger OFC volume in binge-eating disorder patients compared to healthy controls (Schäfer, Vaitl, & Schienle, 2010). First evidence suggests that individual differences in OFC thickness partly mediate the genetic risk for obesity (Opel et al, 2017), possibly by provoking, or failing to inhibit, impulsive and compulsive (eating) behavior.…”
Section: Neural Correlates Of Symptoms Of Food Addiction and Bmimentioning
confidence: 99%
“…More specific to overeating behaviors, reduced OFC gray matter volume and thickness have been related to less restrained eating (Su, Jackson, Wei, Qiu, & Chen, 2017) and unhealthy food choice (Cohen, Yates, Duong, & Convit, 2011), although one study reported larger OFC volume in binge-eating disorder patients compared to healthy controls (Schäfer, Vaitl, & Schienle, 2010). First evidence suggests that individual differences in OFC thickness partly mediate the genetic risk for obesity (Opel et al, 2017), possibly by provoking, or failing to inhibit, impulsive and compulsive (eating) behavior.…”
Section: Neural Correlates Of Symptoms Of Food Addiction and Bmimentioning
confidence: 99%
“…Structural alterations in the OFC have been associated with impaired ability for goaldirected behavior (Reber et al, 2017) and impulsivity (Matsuo et al, 2009) and several studies reported diminished cortical thickness or GMV in the OFC of individuals with substance-related disorders (Durazzo et al, 2011;Ersche et al, 2012;Chye et al, 2017). More specific to overeating behaviors, reduced OFC gray matter volume and thickness have been related to less restrained eating (Su et al, 2017) and unhealthy food choice , although one study reported larger OFC volume in binge-eating disorder patients compared to healthy controls (Schäfer et al, 2010). Structural alterations in OFC thickness could provoke, or fail to inhibit, impulsive and compulsive eating behavior, which would be partially captured by the YFAS symptom score.…”
Section: Neural Correlates Of Food Addiction and Obesitymentioning
confidence: 99%